Osteoarthritis pain: What are we learning from animal models? - Miller, Rachel E. (Best Pract Res Clin Rheumatol, 2018)
All experimental models of osteoarthritis (OA)-like joint damage are accompanied by behaviors indicative of pain. In experimental knee OA, evoked pain responses to exogenously applied stimuli suggest that animals become sensitized to mechanical stimuli. Neurobiological techniques, including electrophysiology and in vivo calcium imaging, confirm that joint damage is associated by peripheral sensitization to mechanical stimuli. Several mediators present in the OA joint can cause peripheral sensitization, most notably the neurotrophin, nerve growth factor. Furthermore, experimental OA is associated with neuro-inflammation in the peripheral and central nervous systems, including macrophage infiltration of the dorsal root ganglia and microglial activation in the spinal cord. Increasingly, researchers are employing models that are slowly progressive, and this approach has revealed that distinct pain mechanisms operate in a time-dependent manner, which may have important translational significance. While the study of pain in experimental OA is rapidly evolving, applying increasingly sophisticated techniques to assess pain and unravel the neurobiology of its genesis, important gaps and limitations in our current approaches exist, which our research community needs to address.